Data rights relevant to weapon systems in Air Force Special Operations Command - Camm, Frank A. 1949- (RAND Project Air Froce, 2021)
The small fleets of specialized aircraft operated by Air Force Special Operations Command (AFSOC) need to be modified quickly to address new threats as they arise. To do this, AFSOC depends heavily on the original equipment manufacturers (OEMs) of its core military aircraft assets and their subsystems for life-cycle support. But AFSOC has grown dissatisfied with the support it is getting from the OEMs in terms of technical data. AFSOC believes that better access to technical data could improve competition for sustainment services or enable the U.S. Air Force to establish organic maintenance capabilities. To make use of a contractor's technical data, the U.S. government must satisfy two conditions. First, the government must have the appropriate license rights. Standardized data rights are based on the source of funding used to create the data. Second, the government must actually possess the data it seeks to use. Securing the data themselves is as important-if not more so-as having the appropriate data rights. In the programs the authors examined, they found limited understanding of the role of data rights and deliverables. In some cases, government personnel inappropriately acceded to contractor claims about what rights the government could acquire. In others, personnel acquired the appropriate data rights but failed to list technical data as deliverables or failed to take delivery of technical data before relevant contract authority expired. Still in other cases there were disputes between the government and contractors over rights. Lack of access to relevant technical data complicated these programs' abilities to sustain their weapon systems
Keywords: Geschichte; Funktionalität; Waffensystem; Datenschutz; Luftwaffe; Rüstungsindustrie; USA; United States / Air Force / Procurement / Evaluation; United States / Air Force Special Operations Command; Airplanes, Military / Modification / United States; Airplanes, Military / Electronic equipment / United States; Intellectual property / United States; United States / Air Force; Airplanes, Military / Electronic equipment; Airplanes, Military / Modification; Armed Forces / Procurement / Evaluation; Intellectual property; United States